2020
DOI: 10.1016/j.scitotenv.2020.138540
|View full text |Cite
|
Sign up to set email alerts
|

Changes in air quality during the lockdown in Barcelona (Spain) one month into the SARS-CoV-2 epidemic

Abstract: Journal Pre-proof J o u r n a l P r e -p r o o f Abstract Lockdown measures came into force in Spain from March 14th, two weeks after the start of the SARS-CoV-2 epidemic, to reduce the epidemic curve. Our study aims to describe changes in air pollution levels during the lockdown measures in the city of Barcelona (NE Spain), by studying the time evolution of atmospheric pollutants recorded at the urban background and traffic air quality monitoring stations. After two weeks of lockdown, urban air pollution mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

106
651
8
18

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 725 publications
(827 citation statements)
references
References 6 publications
106
651
8
18
Order By: Relevance
“…The lockdown has led to a reduction of air pollutants mainly due to the low density of vehicles circulating in cities such as Milan, Italy, resulting in a sharp decrease in SO 2 and NO x ; however, O 3 concentrations tended to increase because of low NO concentrations in the ambient air (Collivignarelli et al 2020 ). This finding is consistent with another study in Barcelona, Spain (Tobías et al 2020 ), in which O 3 concentrations increased by up to 50%. In Sao Paulo, Brazil, the levels of pollutants at an urban site significantly declined during the lockdown period by 77% (NO), 54% (NO 2 ), and 65% (CO) compared with a 5-year monthly mean (Nakada and Urban 2020 ).…”
Section: Introductionsupporting
confidence: 93%
See 1 more Smart Citation
“…The lockdown has led to a reduction of air pollutants mainly due to the low density of vehicles circulating in cities such as Milan, Italy, resulting in a sharp decrease in SO 2 and NO x ; however, O 3 concentrations tended to increase because of low NO concentrations in the ambient air (Collivignarelli et al 2020 ). This finding is consistent with another study in Barcelona, Spain (Tobías et al 2020 ), in which O 3 concentrations increased by up to 50%. In Sao Paulo, Brazil, the levels of pollutants at an urban site significantly declined during the lockdown period by 77% (NO), 54% (NO 2 ), and 65% (CO) compared with a 5-year monthly mean (Nakada and Urban 2020 ).…”
Section: Introductionsupporting
confidence: 93%
“…In addition, several previous studies have shown that the concentrations of PM 2.5 and PM 10 sharply decreased during the COVID-19 lockdown. These reductions of the CAP levels are one of the positive effects of the COVID-19 lockdown on the environment, not considering the negative ones on the socio-economy (Chauhan and Singh 2020 ; Mahato et al 2020 ; Tobías et al 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…pandemic caused a series of lockdown measures on most of the countries it affected that led into a great reduction in personal mobility, goods shipping and industry production. Along with the reduction in transportation, there has been an air pollution reduction observed in Spain [26]. COVID-19 infections clearly play a role in the host immune response mainly through modifying cytokine production resulting in pulmonary tissue damage and the immune insu ciency that may increase viral replication [27].…”
Section: Change In Epidemiological Patternmentioning
confidence: 99%
“…Studies by various scholars have shown how the lockdown has improved the ambient air quality, like in India (Gautam 2020;Mahato et al 2020;Sikarwar and Rani 2020;Srivastava et al 2020), U.S. (Berman and Ebisu 2020), Mexico (Méndez-Arriaga 2020), Kazakhstan (Kerimray et al 2020), Iran (Abdul Halim et al 2018),China (Fan et al 2020; Zambrano-monserrate et al 2020) especially in Wuhan (Cole et al 2020;Lu et al 2020;Sicard et al 2020;Song et al 2016; Q. Wang and Su 2020), Barcelona in Spain (Tobías et al 2020), Sao-Paulo in Brazil (Nakada and Urban 2020), Milan in Italy (Collivignarelli et al 2020), and Salé City in Morocco (Otmani et al 2020) In India, air pollution has become a topic of intense debate at all levels mainly because of the enhanced anthropogenic activities e.g. rapid urbanization, higher population growth, increased energy consumption, and vehicular emission and industrial emission (Dadhich et al 2018;Ghose et al 2005;Gupta et al 2008).…”
Section: Introductionmentioning
confidence: 99%